The Impact of Household Hazardous Waste upon the Environment Pollution - Sarkees, alaa; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2006)
Objectives: To determine the impact of the household hazardous waste’s aspects upon the environment pollution .and to identify the relationship between the households’ demographic characteristics and the aspects of household hazardous waste. Methodology: A descriptive study is conducted between December 14th 2004 to October 20th 2005that uses of an assessment tool. A probability (simple random sampling) of (336) principal’s households which is selected from the zones around the (14) primary health care centers as focal points, (8) in the urban and (6) in the rural areas of Baghdad Governorate. After reliability and validity were determined Data are collected through the use of an assessment tool that is consisted of households’ demographic characteristics and factors that produce household hazardous waste, awareness towards such waste, and management of this waste. Data is performed through the use of descriptive statistical approach (frequencies and percentages) and inferential statistics (stepwise multiple regression analysis). Results: The findings reveal that the aspect of awareness towards household’s hazardous waste has a greater impact upon the household hazardous waste than factors that produce this waste and management of such waste. The study concludes that Low-educated, being in extended family and living with moderately oriented socioeconomic status have influenced the households’ awareness towards their hazardous waste and identification of factors that contribute to such waste and their management of this waste. Recommendation: The study recommends that the Public Awareness Programs can be designed, constructed and presented to increase their awareness towards identification of factors that produce such waste and its management.